IASS’ historie: En personlig fortelling - Garton, Janet (Scandinavistica Vilnensis, 2023)
As the official historian of the International Association for Scandinavian Studies, and one of the two authors of The History of the International Association of Scandinavian Studies 1956–2006, I have been asked to tell the story of the almost 70 years of our association’s existence. The whole thing began in Cambridge in July 1956, as an informal meeting of 65 academics, most of them from the Nordic countries or the United Kingdom; on that occasion there was a grand total of 13 lectures. Since that time there has been a conference every other summer – until the summer of 2020, when it had to be postponed for a year due to the pandemic. It was agreed from the very earliest days that the meetings would be held in a Nordic country and a non-Nordic country alternately, although it was not until 1962, in Aarhus, that IASS was given its official name, and supplied with a constitution and a committee (president, secretary, treasurer etc.) For the early conferences the theme was exclusively literary, but in more recent times it has been expanded to take in other disciplines, such as history, sociology, film studies etc. In 1986 Elias Bredsdorff published a slim volume about the first thirty years of IASS, which I supplemented in 2006 with an account of the following twenty years. I have attended every single conference since 1970, so my talk will provide an extremely personal account of how IASS has become a part of my own history.
Keywords: History of the International Association of Scandinavian Studies; Elias Bredsdorff; Janet Garton; personal history